The Influence of Leadership, Work Motivation, and Job Satisfaction on Employee Performance: Evidence from Universitas MH. Thamrin - Rivanto, Rinto (Priviet Social Sciences Journal, 2022)
This study aims to analyze the influence of leadership, work motivation, and job satisfaction on employee performance at Universitas MH. Thamrin. The research employs a quantitative approach using a survey method, with data collected from 76 employees through structured questionnaires. The data were analyzed using simple and multiple linear regression to examine both partial and simultaneous effects of the independent variables on employee performance. The results indicate that leadership, work motivation, and job satisfaction each have a positive and significant effect on employee performance. Among these variables, work motivation demonstrates the strongest influence, followed by job satisfaction and leadership. The regression analysis shows that all variables contribute meaningfully to improving employee performance, both individually and collectively. The simultaneous test further confirms that the three variables significantly influence performance with a high explanatory power. These findings suggest that organizations should prioritize strengthening leadership practices, enhancing employee motivation, and improving job satisfaction to achieve optimal performance outcomes. An integrated approach in managing these factors is essential, as their combined effect is significantly stronger than their individual contributions. This study provides empirical evidence that leadership, motivation, and job satisfaction are key determinants of employee performance in the context of higher education institutions.